Factors That Influence The Occurrence Of Stunting In Toddlers In Jamang Village, Maduran District, Lamongan - Farras Rosya; Siswari Yuniarti; Irfany Nurul H; Dwi Utari Widyastuti (Global Ten Public Health and Nursing Journal, 2025)
ABSTRACT Introduction : Stunting is a major obstacle to the growth and development of children under 5 years of age, leading to an increased risk of morbidity and mortality, reduced physical capacity, impaired development, and impaired motor function. If left untreated, it can lead to decreased brain development, impaired intelligence, impaired physical growth, and health problems such as the risk of diabetes, obesity, heart disease, cancer, stroke, and disability in old age. The aim of this study was to identify factors influencing stunting in toddlers.Method:This study employed a quantitative descriptive method. The sample consisted of 35 mothers of stunted toddlers. The sampling technique used was total sampling. Data were collected from May 22nd to 25th at the Jamang Village Toddler Health Post (Posyandu) using a questionnaire.Results and Analysis:The results of this study found that the direct factor causing stunting in toddlers in Jamang Hamlet was that most of the toddlers had experienced moderate or severe infections. Meanwhile, the indirect factor causing stunting was maternal occupation. In fact, stunting was more common in toddlers whose mothers were housewives. Conclusion : Mothers of toddlers are expected to consistently monitor and pay attention to their children's health to ensure their growth and development are not disrupted. Increase awareness through health cadres or healthcare workers by providing health education through various media such as leaflets, posters, and videos. This education includes explanations on how to address stunting in toddlers..